2017
DOI: 10.1371/journal.pone.0178585
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose, non-supervised, health insurance initiated exercise for the treatment and prevention of chronic low back pain in employees. Results from a randomized controlled trial

Abstract: ObjectiveBack pain is a major problem requiring pragmatic interventions, low in costs for health care providers and feasible for individuals to perform. Our objective was to test the effectiveness of a low-dose 5-month exercise intervention with small personnel investment on low back strength and self-perceived pain.MethodsTwo hundred twenty-six employees (age: 42.7±10.2 years) from three mid-size companies were randomized to 5-month non-supervised training at home (3 times/week for 20 minutes) or wait-list-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 46 publications
0
21
0
2
Order By: Relevance
“…Recently, a large randomized controlled trial (RCT) of a mobile Web app by Irvine et al reported a significant decrease in pain burden following long-term use of a medical app [ 10 ]. And yet, another recent study confirmed that non-supervised exercise exerted a beneficial effect on pain levels and muscle strength as compared to patients on a wait-list [ 15 ]. Thus, the finding that self-management of LBP with an app reduced user reported pain levels fits well with these earlier observations and published data.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large randomized controlled trial (RCT) of a mobile Web app by Irvine et al reported a significant decrease in pain burden following long-term use of a medical app [ 10 ]. And yet, another recent study confirmed that non-supervised exercise exerted a beneficial effect on pain levels and muscle strength as compared to patients on a wait-list [ 15 ]. Thus, the finding that self-management of LBP with an app reduced user reported pain levels fits well with these earlier observations and published data.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of intervention based on physical exercise, a quite high dispersion of effect size can be noted: large size effect for Jay et al 39 ) ; and low effect for Magalhães et al 42 ) and Staal et al 47 ) . Intervention by physical exercise in Haufe et al 35 ) and Jakobsen et al 37 ) showed a similar medium effect size. In Haufe et al 35 ) , non-supervised exercises, according to exercise planning and guidance by a physiotherapist, were instructed.…”
Section: Discussionmentioning
confidence: 75%
“…Intervention by physical exercise in Haufe et al 35 ) and Jakobsen et al 37 ) showed a similar medium effect size. In Haufe et al 35 ) , non-supervised exercises, according to exercise planning and guidance by a physiotherapist, were instructed. In Jakobsen et al 37 ) , one intervention group performed supervised exercises at work during working hours and another did so at home at their leisure.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[2] Certain studies have displayed the effectiveness of non-supervised exercise in the reduction of chronic low back pain and functionality at work. [9] Exercise therapy has been shown to be more cost-effective than other treatments in the treatment of chronic and subacute low back pain. [10] However, few studies have explored the effectiveness of unsupervised, home-based exercises in patients with subacute LBP.…”
mentioning
confidence: 99%